DESAIN SISTEM INFORMASI PENILAIAN KINERJA AKADEMIK DOSEN (Uji pada STMIK PPKIA Pradnya Paramita Malang) - Husni, Mochamad (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Academic performance appraisal conducted by several agencies to get regular reports about ongoing activities and support the management or decision-makers in subsequent decisions. Given this assessment, is expected to produce data that is more detailed and valid. So that will improve the quality of academic performance in these institutions. From the analysis in the design of Information System Performance Assessment of Academic Lecturers at trial in the High School of Information Management and Computers (STMIK) PPKIA Pradnya Paramita Malang, there is a shortage, especially in the assessment of academic performance so that the lecturer in determining the ability of academic faculty development policy experience obstacles. To facilitate the institution, faculty, and students, then STMIK PPKIA Pradnya Paramita Malang requires a performance assessment system that is more measurable academic lecturer, accurate and more up to date and the assessment of academic performance will be able to assist parties involved, especially the quality assurance and can also used as one part of the filing of the certification lecturers.Â Keywords: Reviewing, Academic Performance